The Perceived Students Opinion on Post-Graduate Job oppurtunities: Finding From UIN Ar-Raniry Islamic Communication and Broadcasting Master Programme - Ridwan Muhammad Hasan; Jailani Jailani; Jasafat Jasafat (Ar-Raniry State Islamic University, Indonesia, 2022)
This research is a descriptive study that examines the development of Postgraduate Study Programs as well as to revitalize and to determine perceptions of study program work opportunities. Islamic Communication and Broadcasting Postgraduate at UIN Ar-Raniry, the alumni to become practitioners of political communication in various fields of the world of work, both government and private lines, are the study program of Islamic Communication and Broadcasting (KPI). To make it even simpler, the researcher made only two problem formulations; How to revitalize job opportunities for study program postgraduate students. Postgraduate Islamic Communication and Broadcasting Becomes a Political Communication Practitioner for the 2016/2018 class. And how is the process and influence of perceptions of interest in job opportunities into political communication on interest in choosing postgraduate Islamic communication and broadcasting study programs at UIN Ar-Raniry Banda Aceh. In this study, researchers used a data collection technique using a tracer study because this technique was not only useful for the internal Postgraduate Study Program of Islamic Communication and Broadcasting, Ar-Raniry State Islamic University, but also became a bridge between the Postgraduate and stakeholders. Tracer studies. Tracer Study to be able to measure and track the performance and suggestions of graduates and graduate users so that clear indicators can be obtained about the number, future job profiles, and competencies required by the world of work